2022
DOI: 10.3390/ijms232112835
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Synovial Cytokine Profile Associated with Long-Term Clinical Outcomes in Patients with Knee Osteoarthritis Undergoing Corrective Osteotomy with Platelet-Rich Plasma or Stromal Vascular Fraction Post-Treatments

Abstract: Functional outcomes and synovial fluid (SF) cytokine concentrations in response to platelet-rich plasma (PRP) or stromal vascular fraction (SVF) post-treatments following open wedge high tibial osteotomy (HTO) in 20 patients with knee osteoarthritis (OA) were examined. Six weeks after surgery, the knees of 10 patients were injected with autologous PRP (PRP subgroup), while another 10 patients were injected with autologous SVF (SVF subgroup) and monitored for 1.5 years. Pain assessment (VAS score) and functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Our previous investigation in the same cohort of patients revealed that the PRP subgroup performed better in terms of KOOS, KSS, and VAS scores compared to the SVF subgroup. However, the SVF subgroup showed superior results in Outerbridge and Koshino testings, leading to more pronounced cartilage regeneration in the medial condyle while slowing down cartilage destruction in its lateral counterpart [26].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Our previous investigation in the same cohort of patients revealed that the PRP subgroup performed better in terms of KOOS, KSS, and VAS scores compared to the SVF subgroup. However, the SVF subgroup showed superior results in Outerbridge and Koshino testings, leading to more pronounced cartilage regeneration in the medial condyle while slowing down cartilage destruction in its lateral counterpart [26].…”
Section: Introductionmentioning
confidence: 88%
“…The open wedge high tibial osteotomy procedure was carried out following established protocols and is described in detail in our previous study involving the same patient cohort [26]. Weight bearing on the operated joint was restricted for up to six weeks post-surgery.…”
Section: Surgical Techniquesmentioning
confidence: 99%
See 3 more Smart Citations